PTU-299 Delivering cost effective management for irritable bowel syndrome (ibs) across somerset. (22nd June 2015) - Greig, E; Gore, S; Staveley, K; Phillips, I; Benneyworth, R; Matull, R; Thole, S; Williams, M
Abstract : Introduction: Despite 2008 NICE guidance on managing IBS in primary care, referrals to gastroenterology persist with baseline audit finding 14% of new outpatient slots in two DGHs were used by patients aged 16–45 years with no red flag symptoms where the GP felt diagnosis at referral was IBS. Given evidence for lifestyle and diet modification, we set out to help GPs avoid referral as outpatient review and investigation cost over £160, 000 annually for these patients. Using potential savings, we funded direct GP access to faecal calprotectin (FC) testing and specialist IBS dietetic-led clinics in four centres across Somerset. Method: We designed new care pathways for 16–45 year olds with no red flag symptoms with county-wide GP education using Rome III criteria to make a positive diagnosis of IBS and avoid missing red flags. Instead of referring to secondary care, GPs were asked to check FC, with Coeliac screen, FBC, CRP and TFT. If FC <50 mg/g with normal blood tests, GPs and community-based dietitians were encouraged to manage symptoms using first-line diet and lifestyle advice, referring to the specialist IBS dietetic clinic if needed. If FC >50 µg/g, secondary care referral was appropriate to consider investigation, especially if FC >150 µg/g. A management algorithm provided symptom-based drug therapies. To aid implementation, the Somerset Pathway Navigator provided a single gateway to GP referrals. Results: Outpatient data: Repeating our initial audit at 1 year showed referrals to secondary care for management and investigation fall from 14% to 9% of new appointments. Faecal calprotectin: 94 patients met this protocol; 64 patients had FC <50 µg/g, 19 had FC 51–150 µg/g and 11 had FC >150 µg/g. Even when FC <50 µg/g, 13 patients were still referred for secondary care review and investigation with no GI pathology found. Only 1/12 patients referred with FC 51–150 mg/g had Crohn's; others had normal endoscopy/radiology. This contrasts with FC >150 mg/g with 10 referred and 5 having Crohn's or Ulcerative colitis. Specialist Dietetic outcomes: Over 12 months, 83 patients completed 8-week treatment courses including low FODMAP advice with statistically significant reductions in severity scores of all symptoms. After treatment, 65% reported satisfactory relief of IBS and 74% reported improved quality of life. Conclusion: Providing GP education, developing new diagnosis and management pathways, introducing FC testing for GPs and effective dietetic treatments have encouraged self-management, provided cost-effective symptom resolution and reduced unnecessary secondary care referrals for likely IBS. Disclosure of interest: None Declared. Reference: Irritable bowel syndrome in adults (2008) CG61 NICE